1997
DOI: 10.1152/jappl.1997.83.6.1849
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surfactant proteins SP-B and SP-C on dynamic and static mechanics of immature lungs

Abstract: To investigate the effects of surfactant proteins B (SP-B) and C (SP-C) on lung mechanics, we compared tidal and static lung volumes of immature rabbits anesthetized with pentobarbital sodium and given reconstituted test surfactants (RTS). With a series of RTS having various SP-B concentrations (0-0.7%) but a fixed SP-C concentration (1.4%), both the tidal volume with 25-cmH2O insufflation pressure and the static volume deflated to 5-cmH2O airway pressure increased, significantly correlating with the SP-B conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 31 publications
0
20
1
Order By: Relevance
“…Some researchers have suggested that a phospholipid mixture combined with SP-B only had the same potency as modified natural surfactants containing both SP-B and SP-C (26,27). In a previous study of ours using surfactant-deficient immature rabbit fetus, however, we found that both SP-B and SP-C are indispensable for yielding high tidal volume (12). In a series comparing reconstituted surfactants containing a fixed concentration of SP-C (1.4%) and various concentrations of SP-B ranging from 0% to 0.7%, it was found that surfactant lacking SP-B yielded lower tidal volumes than other surfactants containing SP-B, although the concentration of SP-C was twice that contained in MNS.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Some researchers have suggested that a phospholipid mixture combined with SP-B only had the same potency as modified natural surfactants containing both SP-B and SP-C (26,27). In a previous study of ours using surfactant-deficient immature rabbit fetus, however, we found that both SP-B and SP-C are indispensable for yielding high tidal volume (12). In a series comparing reconstituted surfactants containing a fixed concentration of SP-C (1.4%) and various concentrations of SP-B ranging from 0% to 0.7%, it was found that surfactant lacking SP-B yielded lower tidal volumes than other surfactants containing SP-B, although the concentration of SP-C was twice that contained in MNS.…”
Section: Discussioncontrasting
confidence: 47%
“…A modified natural surfactant (MNS) was isolated from porcine lungs by broncho-alveolar lavage, chloroform-methanol extraction and acetone precipitation (12). This surfactant consisted of phospholipids (98% in weight), Fatty acids (0.4%), neutral lipids (0.5%), and hydrophobic SPs (1.1%) consisting of SP-B (0.37%) and SP-C (0.72%) (12). MNS was dissolved in chloroform-methanol (1:1, vol/vol) containing 0.1 N hydrochloric acid at a concentration of 5%.…”
Section: Preparation Of Modified Natural Surfactant (Mns) and Synthetmentioning
confidence: 99%
“…This effect was not reproduced with SP-A and was partially reproduced by SP-C. In a similar experiment, the mechanical properties of the lungs improved in a doserelated manner as increased concentrations of SP-B were added to surfactant [29]. Surfactant analyses have shown poractant to have 2-3.7 mg of SP-B per mmol phospholipid, compared to beractant, which has 0-1.3 mg/mmol phospholipid [27].…”
Section: Discussionmentioning
confidence: 99%
“…This effect was not reproduced with SP‐A and was partially reproduced by SP‐C. In a similar experiment, the mechanical properties of the lungs improved in a dose‐related manner as increased concentrations of SP‐B were added to surfactant 29. Surfactant analyses have shown poractant to have 2–3.7 μg of SP‐B per μmol phospholipid, compared to beractant, which has 0–1.3 μg/μmol phospholipid 27.…”
Section: Discussionmentioning
confidence: 93%